Gender implicit bias and glass ceiling effects. Issue 1 (31st December 2022) - Espinosa, María Paz; Ferreira, Eva
ABSTRACT: Implicit gender bias may affect hiring and promotion decisions, implying inefficiencies in the outcome of selection processes. We focus on the dynamics of gender bias when selecting candidates for a committee or position, and obtain the long-run female share as well as the conditions for a glass ceiling effect in a hierarchical structure. Candidate selection is modeled as a Markov process, where the outcome of the dynamic selection process is affected by bias asymmetries and incumbency advantages. Moreover, we formalize and characterize different types of glass ceiling, analyze how the gap between the groups evolves in the corporate hierarchy and show that the dynamics of promotion may indeed generate glass ceilings.